Polysaccharide-based Fibers and Composites Chemical and Engineering Fundamentals and Industrial Applications (Springer International Publishing, 2018)
This book includes chapters based on the potential uses of polysaccharides such as fibers in food and non-food applications. The complexity of their synthesis in plants, the highly multidisciplinary character of polysaccharide research, and the wide variety of applications from food to clothing to energy are addressed in this volume. The authors describe in detail how these latter grand challenges are of great importance in research, especially in the midst of enormous overpopulation and economic issues. Therefore, the volume contributes additional information to the chemical, nutritional, medical, and energy roles of these bio-based products, finding applications in diverse fields of their raw and composite forms. This volume is a useful resource for graduate students and contains themes for instructors and senior research leaders. Written by internationally renowned experts, it is aimed at workers in polymer laboratories, classrooms, and policy makers.